Clinical Outcomes in Patients on Hemodialysis with Congestive Heart Failure - Xinju Zhao; Liangying Gan; Qingyu Niu; Fan Fan Hou; Xinlin Liang; Xiaonong Chen; Yuqing Chen; Junhui Zhao; Keith McCullough; Zhaohui Ni; Li Zuo (Karger Publishers, 2023)
Introduction: Congestive heart failure (CHF) is one of the common complications in patients with end-stage kidney disease. In the general population, CHF increases the risk of the death. However, there is no well-designed relevant study in the Chinese hemodialysis (HD) population addressing the risks associated with CHF. The aim of this study was to explore the impact of CHF on clinical outcomes in HD patients. Methods: Data from a prospective cohort study, the China Dialysis Outcomes and Practice Patterns Study (DOPPS) 5 (2012-2015), were analyzed. Demographic data, comorbidities, lab data, and death records were extracted. CHF was defined by the diagnosis records upon study inclusion. Our primary outcome was all-cause and cardiovascular (CV) mortality; secondary outcomes were all-cause and cause-specific hospitalization risk. Associations between CHF and outcomes were evaluated using Cox regression models. Stepwise multivariate logistic regression was used to identify the related risk factors, and subgroup analyses were carried out. Results: Of 1411 patients without missing CHF history information, 24.1% (340) had CHF diagnosis at enrollment. The overall mortality rates were 21.8% vs. 12.0% (p <0.001) in patients with and without CHF during follow-up, respectively. CHF was associated with higher all-cause mortality (adjusted HR: 1.72, 95% CI: 1.17-2.53, p=0.006), and the association with CV death was of similar magnitude (HR: 1.60, 95% CI: 0.91-2.81, p=0.105). CHF patients had more episodes of hospitalization due to heart failure (HR 2.93, 95% CI: 1. 49- 5.76, P<0.01). However, compared with patients without CHF, the all-cause hospitalization risk was not much higher in CHF patients (HR 1.09, 95% CI: 0.90-1.33, P=0.39). Subgroup analysis found that the effect of CHF on all-cause mortality was stronger for male patients, patients with residual renal function, the elderly (≥60 years of age), patients with arteriovenous fistulae vascular accesses, non-diabetic patients, low-flux dialyzer users, and inadequately dialyzed patients (stdKt/V<2). Conclusion: In HD patients, CHF was found to be associated with a higher risk of all-cause mortality and cause-specific hospitalization risk. Further research is needed to identify opportunities to improve care for HD patients combined with CHF.